Facile hydrophobic modification of hydrophilic membranes by fluoropolymer coating for direct contact membrane distillation - Zhang, Yujun (2023)
Membrane distillation (MD) is a promising desalination technology as it is less sensitive to feed's salinity and can handle high-salinity water. However, the industrial application of MD is restricted by the limited availability of cost-effective hydrophobic membranes. This study developed a simple method to fabricate hydrophobic MD membranes through the coating of a fluoroethylene vinyl ether polymer called LUMIFLON™ LF-200. The fluoropolymer was effectively coated on porous nitrocellulose (NC) and nylon membrane through dip-coating followed by a thermal crosslinking. The coating layer was thin and uniform, covering the surface of the whole membrane matrix, while the high porosity and the microstructure of the membranes were still mostly preserved. After modification, the originally hydrophilic NC and nylon membranes were transformed into hydrophobic, with water contact angles of ∼130°. The 12LF-NC membrane showed a high flux of 10.1 kg m−2 h−1 with salt rejection >99.99% over 120 h in the direct contact MD fed with 10 wt% NaCl solution, which outperformed the commercial PVDF membrane. This coating method has the potential to modify various substrates to produce MD membranes with good performance, which broadens the availability of appropriate membranes for MD application.